Efek Hepatotoksisitas Ekstrak Etanol Herba Kompri (Symphytum officinale L.) Terhadap Hewan Uji Kelinci (Oryctolagus cuniculus) Dengan Parameter SGOT dan SGPT - Norma N; Ulfa Triyani A Latif; Syamsidar Usman (Biogenesis: Jurnal Ilmiah Biologi, 2014)
This study aims to determine the hepatotoxic effects of extract ethanol Herba Comfrey the rabbit test animals by measuring levels of SGOT and SGPT. This study used 12 rabbits were divided into 4 groups. The control group (-) given Na.CMC 1% w/v, group I, II, and III were given suspensions of extract ethanol Herba Comfrey with each concentration of 2% w/v, 4% w/v and 8% w/v for 7 days. The results showed that the extract ethanol Herba Comfrey with concentration of 2% w/v, 4% w/v, and 8% w/v effects can cause hepatotoxicity. It is showed from the increase in the average SGOT value in rabbits at 13.96 U/L, 20.63 U/L and 37.13 U/L. and SGPT value of 20.73 U / L, 32.4 U / L and 44.66 U / L. extract Ethanol Herba Comfrey with concentration 8% w / v causes an increase in SGOT and SGPT concentrations higher than the other, and accelerate the liver damage or hepatotoxicity. The higher the concentration, the greater the effect.Keywords: Herba Comfrey, hepatotoxicity, SGOT-SGPT